Interrelation of functional preferences Of laterality in a selected indian population - SUSIE JEYALYN DAVID,; S. RAJASANKAR, (International Journal of Pharma and Bio Sciences, 2017)
Handedness is the most obvious type of cognitive and behavioural asymmetry reported in human beings. It refers to the preference to perform several tasks with one hand rather than the other. Handedness is a manifestation of the extent of anatomical-functional asymmetry in human brain organization. Also, the brain mechanism underlying handedness is such that handedness is contra laterally related to the two hemispheres, left hand to the right hemisphere and right hand to the left hemisphere. There is evidence that left and right handers differ when compared on a variety of behavioural measures. The present study examined the correlation between hand, foot, eye and ear performances in left and right-handers, which showed high significance as these correlations are indicative of the effects of cerebral dominance.